2002
DOI: 10.1039/b201702d
|View full text |Cite
|
Sign up to set email alerts
|

Palladium dimethylsilanedithiolato complex: a precursor for Ti–Pd and Ti–Pd2 heterometallic complexesElectronic supplementary information (ESI) available: experimental details and spectroscopic data for 1, 2 and 3. See http://www.rsc.org/suppdata/cc/b2/b201702d/

Abstract: The silanedithiolato complex Pd(S2SiMe2)(PEt3)2 1 reacted with (C5H5)TiCl3 and TiCl4(thf)2 to produce the heterometallic clusters (C5H5)TiCl(mu-S)2Pd(PEt3)2 2 and TiCl2(S)(mu-S)2Pd2(PEt3)4 3 along with silicon-sulfur bond cleavage, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This leads to a remarkable increase in the stability of silanethiolato complexes. On the other hand, we found that these silanedithiolato complexes reacted with various metal chlorides and acetates under mild conditions. , For example, we previously reported that the reactions of 5 with (C 5 H 5 )TiCl 3 and TiCl 4 (thf) 2 afforded the copper−titanium sulfido clusters (C 5 H 5 ) 2 Ti 2 Cu 6 S 6 (PEt 3 ) 6 and ClTiCu 3 S 3 (PEt 3 ) 4 , respectively . The mixed-metal sulfido cluster synthesis based on complexes described here is the subject of ongoing work.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…This leads to a remarkable increase in the stability of silanethiolato complexes. On the other hand, we found that these silanedithiolato complexes reacted with various metal chlorides and acetates under mild conditions. , For example, we previously reported that the reactions of 5 with (C 5 H 5 )TiCl 3 and TiCl 4 (thf) 2 afforded the copper−titanium sulfido clusters (C 5 H 5 ) 2 Ti 2 Cu 6 S 6 (PEt 3 ) 6 and ClTiCu 3 S 3 (PEt 3 ) 4 , respectively . The mixed-metal sulfido cluster synthesis based on complexes described here is the subject of ongoing work.…”
Section: Resultsmentioning
confidence: 72%
“…Details of data collection and processing and structure solution are given in Table and the Experimental Section. The structures of 4 and 5 have been reported in the preliminary communications and are not repeated in detail here. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single crystals were obtained from a 3:1 pentane:THF mixture upon cooling to −78 °C. M−ESiMe 3 complexes are rare, yet they are powerful synthons for the formation of M−E−M ‘ complexes, due to the preformed M−E bonds, and the existence of reactive pendant trimethylsilyl groups. The molecular structure (Figure ) confirms the presence of terminally coordinated SeSiMe 3 groups [Zn−Se = 2.3785(6), 2.3881(6) Å].…”
mentioning
confidence: 99%